2011
DOI: 10.1021/ic1023086
|View full text |Cite
|
Sign up to set email alerts
|

Co3O4@graphene Composites as Anode Materials for High-Performance Lithium Ion Batteries

Abstract: This paper reports on the synthesis of Co(3)O(4)@graphene composites (CGC) and their applications as anode materials in lithium ion batteries (LIBs). Through a chemical deposition method, Co(3)O(4) nanoparticles (NPs) with sizes in the range of 10-30 nm were homogeneously dispersed onto graphene sheets. Due to their high electrical conductivity, the graphene sheets in the CGC improved the electrical conductivity and the structure stability of CGC. CGC displayed a superior performance in LIBs with a large rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
234
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(240 citation statements)
references
References 40 publications
5
234
1
Order By: Relevance
“…Unfortunately, none of these enabled satisfactory long term stability (maximum 100 cycles), and most of them showed a high 1 st cycle irreversible capacity (see Table 2 ). At the same time, previously reported graphene-containing alloy (e.g., Sn, [ 144 ] SnO 2 [145][146][147][148][149] or Si [150][151][152][153] ), conversion (e.g., Fe 3 O 4 , [154][155][156][157] Co 3 O 4 [158][159][160][161] or CuO [162][163][164] ) and insertion (e.g., TiO 2 [165][166][167][168] or LTO [169][170][171] ) hybrids were further improved. Interestingly, some appealing approaches, such as the use of ternary hybrids (e.g., RGO/SnO 2 /Fe 3 O 4 [ 172 ] or RGO/CNT/ Sn [ 173 ] ), porous 3D (e.g., RGO/Fe 3 O 4 [ 174,175 ] ) and hollow architectures (e.g., RGO/Fe 3 O 4 [ 176 ] and RGO/TiO 2 [ 168 ] ), were introduced.…”
mentioning
confidence: 75%
“…Unfortunately, none of these enabled satisfactory long term stability (maximum 100 cycles), and most of them showed a high 1 st cycle irreversible capacity (see Table 2 ). At the same time, previously reported graphene-containing alloy (e.g., Sn, [ 144 ] SnO 2 [145][146][147][148][149] or Si [150][151][152][153] ), conversion (e.g., Fe 3 O 4 , [154][155][156][157] Co 3 O 4 [158][159][160][161] or CuO [162][163][164] ) and insertion (e.g., TiO 2 [165][166][167][168] or LTO [169][170][171] ) hybrids were further improved. Interestingly, some appealing approaches, such as the use of ternary hybrids (e.g., RGO/SnO 2 /Fe 3 O 4 [ 172 ] or RGO/CNT/ Sn [ 173 ] ), porous 3D (e.g., RGO/Fe 3 O 4 [ 174,175 ] ) and hollow architectures (e.g., RGO/Fe 3 O 4 [ 176 ] and RGO/TiO 2 [ 168 ] ), were introduced.…”
mentioning
confidence: 75%
“…Graphene nanosheets have high conductivity, large area, and a rich porous texture, which makes the material fl exible and able to be used as a confi ning structure with substantial buffering capability to reduce electrode pulverization. Mn 3 O 4 -graphene, [ 23 ] Co 3 O 4 -graphene [ 24 ] and Fe 3 O 4 /graphene [25][26][27] anode materials have been studied for LIBs, and all of them showed positive effects. For the Fe 3 O 4 /graphene systems, [ 28 , 29 ] the results showed that the effect of the structure of graphene on the LIBs properties is remarkable, and it is possible to improve it by changing the structures and shapes of the composites.…”
Section: Doi: 101002/adma201102838mentioning
confidence: 99%
“…Due to the poor electronic conductivity of Co3O4, various attempts have been made to improve the stable capacities and rate performance of Co3O4 anodes [199], including the addition of highly conducting additives such as graphene [199][200][201][202][203] and silver nanoparticles [204]. For example, Co3O4 nanoparticles (10-30 nm), anchored on graphene sheets displayed a considerably improved rate performance compared to bare Co3O4 samples at the same rate (Fig.…”
Section: Iron Oxidesmentioning
confidence: 99%